Somehistorical andlegal aspects ofthe criminal justice system (International relations and international law Journal, 2016)
This article discussessome historical and legalaspects of the formationofinternational criminal justice. International Criminal process – anactivity carried out by international judicial bodies aimed at curbing international crime, public danger which is recognized by the international community, and to prosecute those responsible for committing them. International criminal process is an activity on the application of international law, as its legal norms and principles, which are fundamental for peace, protection of the individual and the vital interests of the international community as a whole from particularly dangerous for human civilization violations of the principles and norms of international law. There aregeneral patternsand the basicreasons for the formationofinternational criminal justice.Analysis of the sepatternswith the historical andlegal point of viewallows us to understandthe peculiarities of international criminal  juris dictionscurrently
Keywords: international criminal justice; international criminalcourts; international criminal tribunal; international crimes